Web-Based Student Grade Progress Monitoring Information System - Muhammad Khoirur Roziqin; Nuril Lutvi Azizah; Metatia Intan Mauliana; Arif Senja Fitrani (CV. Media Digital Publikasi Indonesia, 2025)
In this study, the researchers found a way to help teachers input student grades and achievements. Currently, records are still kept in books, which can cause problems such as burning, deterioration over time, or damage caused by pests. The purpose of this study is to create a system that can be a solution to the above problems, which will also make it easier for teachers to monitor their students so that they can report to the students' guardians. The researcher hopes that this system can help in monitoring student development. Blackbox testing was conducted to show that all features functioned as expected. In addition, a user survey was conducted, which showed a satisfactory rating of 60%, particularly for the interface design. However, the system performance still needs improvement because errors occurred in several aspects and received a low satisfaction rating of less than 50%. There are still many shortcomings in this research that need to be addressed. Hopefully, future research can improve on these shortcomings, resulting in a useful project.